REVOLUSI INDUSTRI 4.0 DAN MASA DEPAN PENDIDIKAN ISLAM TRADISIONAL - Umam, Asep Samsul; Shohibuddin, Muhammad Rofi; Selamet (As-Sulthan Journal of Education, 2025)
The Fourth Industrial Revolution has brought profound transformations to nearly all aspects of human life, including social, cultural, and educational spheres. The rapid advancement of digital technology, artificial intelligence, big data, and information automation demands educational systems to adapt swiftly, creatively, and innovatively. Within this context, traditional Islamic education, such as pesantren, faces significant challenges in maintaining its relevance and sustainability. This is largely due to its reliance on classical learning models, such as the study of kitab kuning (classical Islamic texts), the use of traditional methods like sorogan and bandongan, and oral knowledge transmission that involves minimal integration of modern technology. Without strategic responses to these shifts, traditional Islamic education risks being marginalized amid the fast-paced global development. Nevertheless, the Fourth Industrial Revolution should not be viewed solely as a threat, but rather as an opportunity to foster value-based innovation in Islamic education. By integrating more adaptive curricula, utilizing digital technology, and adopting innovative teaching methods while preserving Islamic identity, pesantren and other traditional Islamic institutions can remain relevant, resilient, and even competitive in the global arena. Therefore, the Fourth Industrial Revolution should be regarded not as the end, but as a critical momentum for the revitalization and renewal of traditional Islamic education.